2022
DOI: 10.1186/s13578-022-00935-y
|View full text |Cite
|
Sign up to set email alerts
|

FOXO3a-dependent PARKIN negatively regulates cardiac hypertrophy by restoring mitophagy

Abstract: Background Sustained cardiac hypertrophy often develops maladaptive myocardial remodeling, and eventually progresses to heart failure and sudden death. Therefore, maladaptive hypertrophy is considered as a critical therapeutic target for many heart diseases. Mitophagy, a crucial mechanism in mitochondria quality control and cellular homeostasis, has been implicated in diverse cardiac disorders such as myocardial infarction, diabetic cardiomyopathy, cardiac hypertrophy and heart failure. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Foxo3a is a transcription factor that essential for cell survival and stress response, which involved in various cellular processes, including apoptosis and mitochondrial dynamics (28). Emerging evidence have demonstrated that Parkin interact with Foxo3a to coordinate mitochondrial dynamics, enhance mitochondrial quality control, and suppress cell apoptosis (42,43). In this study, we found Foxo3a blinds to Parkin and regulates the expression of Parkin protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Foxo3a is a transcription factor that essential for cell survival and stress response, which involved in various cellular processes, including apoptosis and mitochondrial dynamics (28). Emerging evidence have demonstrated that Parkin interact with Foxo3a to coordinate mitochondrial dynamics, enhance mitochondrial quality control, and suppress cell apoptosis (42,43). In this study, we found Foxo3a blinds to Parkin and regulates the expression of Parkin protein.…”
Section: Discussionmentioning
confidence: 99%
“…This hyperactivation of FoxO3a could potentially play a role in the transcriptional regulation of the Parkin pathway as FoxO3a has been identified as a transcriptional regulator of Parkin, influencing cell proliferation, migration, and apoptosis in gastric cancer (21). In addition, Sun et al (43) have reported that FoxO3a regulates Parkin transcription by binding to the consensus sequence within the Parkin gene’s promoter region, thereby playing a critical role in mitophagy and autophagy processes in cardiac hypertrophy . These findings are consistent with ours.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the same study showed that Prdx3 interacts with PINK1 and blocks its proteolytic cleavage during mitophagy, playing a protective role during hypertrophy-induced mitochondrial dysfunction (Sonn et al, 2022). Of note, Parkin levels decline in hypertrophic cardiomyocytes, as well as mouse hearts, and overexpression of Parkin in mice blocked Ang-IIinduced hypertrophy and improved heart function via boosting mitophagy, highlighting the importance of clearance of damaged mitochondria during cardiac hypertrophy (Sun et al, 2022).…”
Section: Cardiac Hypertrophy and Heart Failurementioning
confidence: 99%
“…Echocardiography was carried out as we described previously [32]. In brief, 1-2 weeks after I/R injury, transthoracic echocardiography was performed under 2% iso urane anaesthesia to analyze cardiac structure and function using Prospect High Resolution Imaging System equipped with a 40 MHz probe.…”
Section: Echocardiograpy and Histological Stainingmentioning
confidence: 99%